Análise da reconstrução 3D a partir de um par estereoscópico HR-CCD/CBERS-2 usando dois modelos matemáticos - Galindo, José Roberto Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Desde o advento dos primeiros satélites de Sensoriamento Remoto, vários são os estudos desenvolvidos com o intuito de utilizar as imagens produzidas por estes sensores para fins cartográficos. Apesar das imagens de baixa e média resolução não possuírem a precisão requerida para aplicações cartográficas em escalas grandes, existem vantagens como: serem imagens multiespectrais, possuírem periodicidade e menores custos para a sua aquisição, quando comparadas com as obtidas através dos tradicionais levantamentos aerofotogramétricos. Uma melhoria presente nos satélites de alta e média resolução é a capacidade de visada off nadir, o que permite à formação de pares estereoscópicos e a reconstrução 3D da cena imageada, a geração de modelos digitais de elevação (MDE) e a produção de imagens ortorretificadas, dentre outros produtos. Com os primeiros pares estereoscópicos adquiridos pelo sensor HR-CCD (High Resolution Charge-Coupled Devices) do CBERS-2 (2004), surgiu a possibilidade de realizar estudos objetivando a geração de produtos cartográficos a partir desses estereopares...

Since the advent of the first Remote Sensing satellites, many studies have been developed with the intention of using the images produced by these sensors for cartographic purpose. Although these images of the average resolution do not possess the accuracy required for cartographic applications in big scales, their advantages include being multispectral, periodic repetition of acquisition, and lower cost when compared to images obtained through traditional aerial photogrammetric surveys. An improvement present in medium and high resolution satellites is their off nadir capacity, which allows 3D reconstruction based on stereoscopy, the generation of digital elevation models (DEM) and the production of orthorectified images, among others products. With the first stereoscopic pairs acquired by the CBERS-2 (2004) HR-CCD (High Resolution Charge-Coupled Device) sensor, the possibility now exists of realizing studies whose goal is generating cartographic products from these stereo pairs. Within this context, this work evaluated the geometric quality of a CBERS-2 HR-CCD stereo pair making use of the DLT (Direct Linear Transformation) mathematical model and Polynomial-Based Pushbroom model, available from the Leica Photogrammetry Suite (LPS) digital photogrammetry system by Leica Geosystems, classifying them in accordance with the Cartographic Accuracy Standards... (Complete abstract click electronic access below)
Keywords: Cartografia; Stereopairs HR-CCD/CBERS-2; Digital elevation model; Digital Photogrammetry; Pushbroom sensor; Polynomial model; Direct Linear